Postmortem neocortical 3H‐PiB binding and levels of unmodified and pyroglutamate Aβ in Down syndrome and sporadic Alzheimer's disease. (20th December 2022) - Pivtoraiko, Violetta; Racic, Tamara; Abrahamson, Eric E; Villemagne, Victor L; Handen, Benjamin L; Lott, Ira T; Head, Elizabeth; Ikonomovic, Milos D
Abstract: Background: Individuals with Down syndrome (DS) have a genetic predisposition for amyloid‐β (Aβ) overproduction and earlier onset of Aβ deposits compared to sporadic late‐onset Alzheimer's disease (AD). Positron emission tomography (PET) with Pittsburgh Compound‐B (PiB) detects fibrillar Aβ pathology in living people with DS and AD, but its relationship with heterogeneous Aβ forms aggregated within amyloid deposits is not well understood. Method: We performed quantitative in‐vitro 3 H‐PiB binding assays and enzyme‐linked immunosorbent assays of fibrillar (insoluble) unmodified Aβ40 and Aβ42 forms and N‐terminus truncated and pyroglutamate‐modified AβNpE3‐40 and AβNpE3‐42 forms in postmortem frontal cortex and precuneus samples from 18 DS cases aged 43‐63 years and 17 late‐onset AD cases aged 62‐99 years. Result: Compared to the AD group, the DS group had higher levels of Aβ40 and AβNpE3‐40, while the two groups did not differ by Aβ42 and AβNpE3‐42 levels, in both the frontal cortex and precuneus. This resulted in lower ratios of Aβ42/Aβ40 and AβNpE3‐42/AβNpE3‐40 in the DS group compared to the AD group, in both cortical regions. Correlations of Aβ42/Aβ40 and AβNpE3‐42/AβNpE3‐40 ratios with CAA severity were strong in DS cases, and weak in AD cases. The two diagnostic groups did not differ significantly by 3 H‐PiB binding levels in the frontal cortex or in the precuneus. Conclusion: These results demonstrate that compared to late‐onset AD cases, adult DS individuals with similar burden of cortical Aβ plaques have a preponderance of both pyroglutamate‐modified AβNpE3‐40 and unmodified Aβ40 forms which are associated with greater CAA pathology. Despite the distinct molecular profile of Aβ forms and greater vascular amyloidosis in DS cases, cortical 3 H‐PiB binding does not distinguish between diagnostic groups that are at an advanced level of amyloid plaque pathology. These results underscore the need for development of CAA‐selective PET radiopharmaceuticals in order to detect and track the progression of cerebral vascular amyloid deposits in relation to Aβ plaques at the earliest pathology stages in individuals with DS.